Bacterial community structures and dynamics associated with rotated positioning syndrome in gilthead sea bream (Sparus aurata) larviculture - Bel Mokhtar, Naima; Apostolopoulou, Georgia; Koumoundouros, George; Tzokas, Kostas; Toskas, Kosmas; Gourzioti, Evgenia; Stathopoulou, Panagiota; Tsiamis, George (Frontiers in Aquaculture, 2024)
Introduction The availability of high-quality gilthead seabream (Sparus aurata) larvae in larviculture represents a major bottleneck to the aquaculture. This challenge can be compounded by losses resulting from the emergence of a clinical disorder’s symptomatology. In this study, the observed syndrome included a rotated positioning of the larval sagittal plane and in most cases leading eventually to death. Methods Herein, we examined using amplicon sequencing of the 16S rDNA the bacterial communities associated with S. aurata larvae at different conditions (including both fish with no evidence of the syndrome and fish with syndrome) during the early developmental stages along with the contribution of rearing water, organic matter and provided feed in the microbiota during an experiment of 18 days. Results Over the development of larvae, differences were observed in the bacterial composition between healthy and symptomatic larvae as well as between components of the system. A remarkable presence of members of the Psychrobacter genus was observed in symptomatic larvae with a significant increase at 18dph. The healthy larvae harbor different bacterial profile with a dominance of Vibrio and Bacillus genera during 3-8dph, various members of Alphaproteobacteria during 11-14dph and Marinifilum at 18dph. The rearing water showed a different bacterial profile compared to the other components, with a slight effect of healthy larvae at 3-8dph. The bacteriome of feeds provided during the rearing of larvae was found to be diverse. Chlorella was mainly dominated by members of Firmicutes, while Rotifer and Artemia were mainly dominated by members of Proteobacteria including different species of Psychrobacter. At 18dph, Artemia feed seems to affect the symptomatic larvae bacteriome, where it enhanced the presence of Psychrobacter spp. Discussion Interestingly, the comparative network analysis at 18dph indicated that the bacterial associations in symptomatic larvae were primarily driven by members of the Psychrobacter genus. While various phyla contributed to bacterial associations in healthy larvae with different frequencies including mainly members of Proteobacteria, Bacteroidota and Firmicutes phyla. Finally, the Gammaproteobacteria/Alphaproteobacteria ratio was found to be related to the health condition of larvae. This study provides valuable information which can be used as indicators for monitoring the health status of S. aurata larvae.